Mutagenic and carcinogenic potency determinations for NDMA support the cumulative dose assumption underpinning the less-than-lifetime Threshold of Toxicological Concern - John W. Wills; Angela White; Danielle S. G. Harte; Ruby Buckley; James S. Harvey; Anthony M. Lynch (Archives of Toxicology, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Functional auxin signaling and phosphorus acquisition induced in planta by the extremophile bacterium Pseudomonas extremaustralis - Carola Agranatti; Jose G. Ibarra; Mariana B. Galeano; Ruby Terranova; Manuel S. Godoy; Nancy I. López; Martiniano M. Ricardi; Paula M. Tribelli (Rhizosphere, 2026)

Tourists’ Circular Behavior and Its Determinants: Pathways Toward Sustainable Destinations - Swati Naik; Ruby S. Chanda (Circular Economy and Sustainability, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Well-designed construction of rare earth ruddlesden-popper oxide confined on reduced graphene oxide nanosheets: A promising electrocatalyst for the monitoring of anthropogenic toxin - Santhiyagu Sahayaraj Rex Shanlee; Muthukumar Govindaraj; Tse-Wei Chen; Shen ming-chen; Arockia Selvi J; Pichai Christina Ruby Stella; Safaa S. Taha; Mohamed Farouk Elsadek; Mohamed S. E. (Process Safety and Environmental Protection, 2026)

Gestational fine particulate matter exposure and perinatal outcomes in the ECHO cohort: Associations across pregnancy windows - Adaeze W. Nzegwu; Aisha S. Dickerson; Kristin Miller; Adam Szpiro; Alison E. Hipwell; Amy J. Elliot; Amy M. Padula; Anne L. Dunlop; Anne P. Starling; Assiamira Ferrara; Carrie V. Breton; Christine T. Loftus; et al. (Environmental Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Integrated Body and Otolith Morphometrics Indicate a Single Stock of Bigeye Scad (Selar crumenophthalmus) in Northern Mindanao, Philippines - Renie M. Magallanes; Lhendy P. De Leon; Rosa Ruby P. Cabiguin; Emmanuel S. Delloro; Adzel Adrian G. Baldevieso; Kaent Immanuel N. Uba (Thalassas: An International Journal of Marine Sciences, 2025)

Modulatory effects of bioactive natural compounds on pruritic pathways: mechanistic basis and therapeutic prospects - Wagih H. Marcus; Hassan A. Ruby; Amira E. Awwad; Mahrous H. Mahrous; Ebraheem Abouelwafa; Mohamed A. S. Badawy; Riham A. El-Shiekh; Eman S. Zaki; Mahmoud Abdelmouti Mahmoud (Inflammopharmacology, 2025)
Chronic pruritus, characterized by persistent itching, is a significant health issue that adversely affects individuals’ quality of life, particularly in palliative care environments. Conventional treatments frequently do not yield sufficient relief and may lead to undesirable side effects, which has spurred interest in exploring alternative therapeutic options. A thorough literature search was conducted across several databases such as PubMed, Web of Science, Scopus, and EKB, with an emphasis on studies involving in vitro, animal models, and clinical trials utilizing terms like “plant,” “extract,” and “pruritus.” All studies were considered regardless of their publication date and were limited to English-language articles. This review highlights the promise of various medicinal plants, including chamomile, Aloe vera , calendula, curcumin, lavender, licorice, and peppermint, as adjunctive therapies for pruritus. These plants possess a range of pharmacological properties, such as anti-inflammatory, antioxidant, and skin-soothing effects, which are relevant to the complex nature of pruritus. Their favorable safety profiles and natural origins enhance their appeal in holistic and patient-centered care models.

Long-term glyphosate application and its effects on soil total nitrogen and microbial composition two years after application stopped in biochar-amended soil - Negar Omidvar; Zhihong Xu; Steven M. Ogbourne; Rebecca Ford; Prabhakaran Thanjavur Sambasivam; Trong D. Tran; Babak Salehin; Ruby N. Michael; Fang Wang; Iman Tahmasbian; Rachele S. Wilson; Shahla Hosseini Bai (Applied Soil Ecology, 2025)

Air pollution exposures and adverse childhood experiences in relation to sleep health in middle childhood - Jonika B. Hash; Logan C. Dearborn; Christine T. Loftus; Catherine J. Karr; Adam A. Szpiro; Emily S. Barrett; Kaja Z. LeWinn; Ruby Nguyen; Paul E. Moore; Brent Collett; Amanda N. Noroña-Zhou; Nicole R. Bush; et al. (International Journal of Hygiene and Environmental Health, 2025)

Exposure to polyoxyethylene tallow amines (POEAs), glyphosate co-formulation surfactants, in a US pregnant population and their potential endocrine disrupting effects - Bushra Amreen; Corina Lesseur; Ravikumar Jagani; Shirisha Yelamanchili; Emily S. Barrett; Ruby H.N. Nguyen; Sheela Sathyanarayana; Shanna H. Swan; Syam S. Andra; Jia Chen (Environmental Pollution, 2025)

Correction to: Rapid root development in clay subsoils enhances the early growth of native grassland species - Katherine Horsfall; Nicholas S. G. Williams; Ruby N. Michael; Stephen J. Livesley (Plant and Soil, 2025)

Rapid root development in clay subsoils enhances the early growth of native grassland species - Katherine Horsfall; Nicholas S. G. Williams; Ruby N. Michael; Stephen J. Livesley (Plant and Soil, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Aerobic thermophilic digestion of fecal matter: Condensate recovery, low solids production, and water reuse - Ruby A. Lai; Sung-Geun Woo; Emir Aksüyek; Latifah Hamzah; Santiago Alvillar; Kartik Chandran; Craig S. Criddle (Bioresource Technology Reports, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

Associations of prenatal ambient air pollution exposures with asthma in middle childhood - Marnie F. Hazlehurst; Kecia N. Carroll; Paul E. Moore; Adam A. Szpiro; Margaret A. Adgent; Logan C. Dearborn; Allison R. Sherris; Christine T. Loftus; Yu Ni; Qi Zhao; Emily S. Barrett; Ruby H.N. Nguyen; et al. (International Journal of Hygiene and Environmental Health, 2024)

Applications and advancements of nanoparticle-based drug delivery in alleviating lung cancer and chronic obstructive pulmonary disease - Gabriele De Rubis; Keshav Raj Paudel; Leander Corrie; Samir Mehndiratta; Vyoma K. Patel; Popat S. Kumbhar; Arehalli Sidramappa Manjappa; John Disouza; Vandana Patravale; Gaurav Gupta; Bikash Manandhar; Rashi Rajput; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Hydrolysate production from sugarcane bagasse using steam explosion and sequential steam explosion-dilute acid pretreatment for polyhydroxyalkanoate fermentation - Hazel Joy C. Barrameda; Princess J. Requiso; Catalino G. Alfafara; Fidel Rey P. Nayve Jr.; Ruby Lynn G. Ventura; Jey-R S. Ventura (Bioactive Carbohydrates and Dietary Fibre, 2023)

Minimal vertical transmission of Equid alphaherpesvirus 1 (EHV-1) in normal developing foals during a naturally occurring abortion outbreak - Amjad Khan; Miguel Blanco; Jennifer Janes; Rebecca Ruby; Ioana Popa; Rocio Vicioso; Lutz S Goehring (Journal of Equine Veterinary Science, 2023)

Prenatal bisphenol A and S exposure and atopic disease phenotypes at age 6 - Abigail Gaylord; Emily S. Barrett; Sheela Sathyanarayana; Shanna H. Swan; Ruby H.N. Nguyen; Nicole R. Bush; Kecia Carroll; Drew B. Day; Kurunthachalam Kannan; Leonardo Trasande (Environmental Research, 2023)

Comprehensive Analysis of the Physiological Characterization of Escherichia coli Nissle 1917 - S. Ramadevi; Ruby Shelin; Meenakshi Shanmugaraja (Current Microbiology, 2023)

The population structure, sex ratio and reproductive potential of limpets (Patella spp.) on natural shores and artificial structures in the Irish Sea - Hannah S. Earp; Ruby George; Paul R. Brooks; Veronica Farrugia Drakard; Bryan J. Thompson; Benjamin Fisher; Róisín Hayden; Tasman P. Crowe; Pippa J. Moore (Marine Environmental Research, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Analysis of positive correlation in magnitude and time measurement for earthquake using electric signals - Oumaima Saidani; Ramkumar Raja Manoharan; Ahmed Samir Naje; Ruby Mishra; Arjun Subburaj; Maheswari S; Mohamed Yacin Sikkandar; Sankar Ganesh Sundaram; Regin Rajan; Sudhakar Sengan (Earth Science Informatics, 2022)

A comprehensive review of dye-sensitized solar cell optimal fabrication conditions, natural dye selection, and application-based future perspectives - Ruby Baby; Peter Daniel Nixon; Nallapaneni Manoj Kumar; M. S. P. Subathra; Nallamuthu Ananthi (Environmental Science and Pollution Research, 2022)

Inter-laboratory automation of the in vitro micronucleus assay using imaging flow cytometry and deep learning - John W. Wills; Jatin R. Verma; Benjamin J. Rees; Danielle S. G. Harte; Qiellor Haxhiraj; Claire M. Barnes; Rachel Barnes; Matthew A. Rodrigues; Minh Doan; Andrew Filby; Rachel E. Hewitt; Catherine A. Thornton; et al. (Archives of Toxicology, 2021)
The in vitro micronucleus assay is a globally significant method for DNA damage quantification used for regulatory compound safety testing in addition to inter-individual monitoring of environmental, lifestyle and occupational factors. However, it relies on time-consuming and user-subjective manual scoring. Here we show that imaging flow cytometry and deep learning image classification represents a capable platform for automated, inter-laboratory operation. Images were captured for the cytokinesis-block micronucleus (CBMN) assay across three laboratories using methyl methanesulphonate (1.25–5.0 μg/mL) and/or carbendazim (0.8–1.6 μg/mL) exposures to TK6 cells. Human-scored image sets were assembled and used to train and test the classification abilities of the “DeepFlow” neural network in both intra- and inter-laboratory contexts. Harnessing image diversity across laboratories yielded a network able to score unseen data from an entirely new laboratory without any user configuration. Image classification accuracies of 98%, 95%, 82% and 85% were achieved for ‘mononucleates’, ‘binucleates’, ‘mononucleates with MN’ and ‘binucleates with MN’, respectively. Successful classifications of ‘trinucleates’ (90%) and ‘tetranucleates’ (88%) in addition to ‘other or unscorable’ phenotypes (96%) were also achieved. Attempts to classify extremely rare, tri- and tetranucleated cells with micronuclei into their own categories were less successful (≤ 57%). Benchmark dose analyses of human or automatically scored micronucleus frequency data yielded quantitation of the same equipotent concentration regardless of scoring method. We conclude that this automated approach offers significant potential to broaden the practical utility of the CBMN method across industry, research and clinical domains. We share our strategy using openly-accessible frameworks.

North American extreme precipitation events and related large-scale meteorological patterns: a review of statistical methods, dynamics, modeling, and trends - Mathew Barlow; William J. Gutowski; John R. Gyakum; Richard W. Katz; Young-Kwon Lim; Russ S. Schumacher; Michael F. Wehner; Laurie Agel; Michael Bosilovich; Allison Collow; Alexander Gershunov; Richard Grotjahn; et al. (Climate Dynamics, 2019)
This paper surveys the current state of knowledge regarding large-scale meteorological patterns (LSMPs) associated with short-duration (less than 1 week) extreme precipitation events over North America. In contrast to teleconnections, which are typically defined based on the characteristic spatial variations of a meteorological field or on the remote circulation response to a known forcing, LSMPs are defined relative to the occurrence of a specific phenomenon—here, extreme precipitation—and with an emphasis on the synoptic scales that have a primary influence in individual events, have medium-range weather predictability, and are well-resolved in both weather and climate models. For the LSMP relationship with extreme precipitation, we consider the previous literature with respect to definitions and data, dynamical mechanisms, model representation, and climate change trends. There is considerable uncertainty in identifying extremes based on existing observational precipitation data and some limitations in analyzing the associated LSMPs in reanalysis data. Many different definitions of “extreme” are in use, making it difficult to directly compare different studies. Dynamically, several types of meteorological systems—extratropical cyclones, tropical cyclones, mesoscale convective systems, and mesohighs—and several mechanisms—fronts, atmospheric rivers, and orographic ascent—have been shown to be important aspects of extreme precipitation LSMPs. The extreme precipitation is often realized through mesoscale processes organized, enhanced, or triggered by the LSMP. Understanding of model representation, trends, and projections for LSMPs is at an early stage, although some promising analysis techniques have been identified and the LSMP perspective is useful for evaluating the model dynamics associated with extremes.

Progress on the phylogeny of the Omphalotaceae: Gymnopus s. str., Marasmiellus s. str., Paragymnopus gen. nov. and Pusillomyces gen. nov. - Jadson J. S. Oliveira; Ruby Vargas-Isla; Tiara S. Cabral; Doriane P. Rodrigues; Noemia K. Ishikawa (Mycological Progress, 2019)

Workers' sons rescue genetic diversity at the sex locus in an invasive honey bee population - Rosalyn S. Gloag; Joshua R. Christie; Guiling Ding; Ruby E. Stephens; Gabriele Buchmann; Benjamin P. Oldroyd (Molecular Ecology, 2019)
The hallmark of eusociality is the division of labour between reproductive (queen) and nonreproductive (worker) females. Yet in many eusocial insects, workers retain the ability to produce haploid male offspring from unfertilized eggs. The reproductive potential of workers has well‐documented consequences for the structure and function of insect colonies, but its implications at the population level are less often considered. We show that worker reproduction in honey bees can have an important role in maintaining genetic diversity at the sex locus in invasive populations. The honey bee sex locus is homozygous‐lethal, and, all else being equal, a higher allele number in the population lead to higher mean brood survival. In an invasive population of the honey bee Apis cerana in Australia, workers contribute significantly to male production: 38% of male‐producing colonies are queenless, and these contribute one‐third of all males at mating congregations. Using a model, we show that such male production by queenless workers will increase the number of sex alleles retained in nascent invasive populations following founder events, relative to a scenario in which only queens reproduce. We conclude that by rescuing sex locus diversity that would otherwise be lost, workers' sons help honey bee populations to minimize the negative effects of inbreeding after founder events and so contribute to their success as invaders.

Heavy metal concentrations in soils and vegetation in urban areas of Quezon City, Philippines - Ian A. Navarrete; Christella C. Gabiana; Joan Ruby E. Dumo; Severino G. Salmo; Maria Aileen Leah G. Guzman; Nestor S. Valera; Emilyn Q. Espiritu (Environmental Monitoring and Assessment, 2017)

Mycological Profile and Antifungal Susceptibility of Fungal Isolates from Clinically Suspected Cases of Fungal Rhinosinusitis in a Tertiary Care Hospital in North India - Ruby Jain; Surinder K. Singhal; Nidhi Singla; Rajpal S. Punia; Jagdish Chander (Mycopathologia, 2015)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Cytotoxicity studies of semi-synthetic derivatives of theveside derived from the aqueous extract of leaves of ‘suicide tree’ Cerbera odollam - Jaggaiah N. Gorantla; Jamsheena Vellekkatt; Lekshmi R. Nath; Ruby John Anto; Ravi S. Lankalapalli (Natural Product Research, 2014)

Non‐native acylated homoserine lactones reveal that LuxIR quorum sensing promotes symbiont stability - Sarah V. Studer; Julia A. Schwartzman; Jessica S. Ho; Grant D. Geske; Helen E. Blackwell; Edward G. Ruby (Environmental Microbiology, 2014)
Summary Quorum sensing, a group behaviour coordinated by a diffusible pheromone signal and a cognate receptor, is typical of bacteria that form symbioses with plants and animals. LuxIR ‐type N ‐acyl L‐homoserine ( AHL ) quorum sensing is common in Gram‐negative Proteobacteria , and many members of this group have additional quorum‐sensing networks. The bioluminescent symbiont V ibrio fischeri encodes two AHL signal synthases: AinS and LuxI . AinS ‐dependent quorum sensing converges with LuxI ‐dependent quorum sensing at the LuxR regulatory element. Both AinS ‐ and LuxI ‐mediated signalling are required for efficient and persistent colonization of the squid host, E uprymna scolopes . The basis of the mutualism is symbiont bioluminescence, which is regulated by both LuxI ‐ and AinS ‐dependent quorum sensing, and is essential for maintaining a colonization of the host. Here, we used chemical and genetic approaches to probe the dynamics of LuxI ‐ and AinS ‐mediated regulation of bioluminescence during symbiosis. We demonstrate that both native AHLs and non‐native AHL analogues can be used to non‐invasively and specifically modulate induction of symbiotic bioluminescence via LuxI ‐dependent quorum sensing. Our data suggest that the first day of colonization, during which symbiont bioluminescence is induced by LuxIR , is a critical period that determines the stability of the V . fischeri population once symbiosis is established.

Synthesis of piperazinyl benzothiazole/benzoxazole derivatives coupled with 1,3,4-oxadiazole-2-thiol: novel hybrid heterocycles as anticancer agents - M. S. R. Murty; B. Ramalingeswara Rao; Mohana Rao Katiki; Lekshmi R. Nath; Ruby John Anto (Medicinal Chemistry Research, 2013)

Genetic variants associated with breast cancer risk for Ashkenazi Jewish women with strong family histories but no identifiable BRCA1/2 mutation - Erica S. Rinella; Yongzhao Shao; Lauren Yackowski; Sreemanta Pramanik; Ruth Oratz; Freya Schnabel; Saurav Guha; Charles LeDuc; Christopher L. Campbell; Susan D. Klugman; Mary Beth Terry; Ruby T. Senie; et al. (Human Genetics, 2013)

Effects of agricultural pesticides on the health of Rana pipiens frogs sampled from the field - M. S. Christin; L. Ménard; I. Giroux; D. J. Marcogliese; S. Ruby; D. Cyr; M. Fournier; P. Brousseau (Environmental Science and Pollution Research, 2013)

Synthesis and preliminary evaluation activity studies of novel 4-(aryl/heteroaryl-2-ylmethyl)-6-phenyl-2-[3-(4-substituted-piperazine-1-yl)propyl]pyridazin-3(2H)-one derivatives as anticancer agents - M. S. R. Murty; B. Ramalingeswara Rao; Kesur R. Ram; J. S. Yadav; Jayesh Antony; Ruby John Anto (Medicinal Chemistry Research, 2012)

Substrate use and biochemical response to a 3,211-km bicycle tour in trained cyclists - Dustin R. Slivka; Charles L. Dumke; Walter S. Hailes; John S. Cuddy; Brent C. Ruby (European Journal of Applied Physiology, 2012)

Polyphyly of non‐bioluminescent Vibrio fischeri sharing a lux ‐locus deletion - M. S. Wollenberg; S. P. Preheim; M. F. Polz; E. G. Ruby (Environmental Microbiology, 2012)
Summary This study reports the first description and molecular characterization of naturally occurring, non‐bioluminescent strains of Vibrio fischeri . These ‘dark’ V. fischeri strains remained non‐bioluminescent even after treatment with both autoinducer and aldehyde, substrate additions that typically maximize light production in dim strains of luminous bacteria. Surprisingly, the entire lux locus (eight genes) was absent in over 97% of these dark V. fischeri strains. Although these strains were all collected from a Massachusetts (USA) estuary in 2007, phylogenetic reconstructions allowed us to reject the hypothesis that these newly described non‐bioluminescent strains exhibit monophyly within the V. fischeri clade. These dark strains exhibited a competitive disadvantage against native bioluminescent strains when colonizing the light organ of the model V. fischeri host, the Hawaiian bobtail squid Euprymna scolopes . Significantly, we believe that the data collected in this study may suggest the first observation of a functional, parallel locus‐deletion event among independent lineages of a non‐pathogenic bacterial species.

Synthesis and preliminary evaluation of 2-substituted-1,3-benzoxazole and 3-[(3-substituted)propyl]-1,3-benzoxazol-2(3H)-one derivatives as potent anticancer agents - M. S. R. Murty; Kesur R. Ram; Rayudu Venkateswara Rao; J. S. Yadav; Janapala Venkateswara Rao; Vino T. Cheriyan; Ruby John Anto (Medicinal Chemistry Research, 2011)

Natural transformation of Vibrio fischeri requires tfoX and tfoY - Amber Pollack‐Berti; Michael S. Wollenberg; Edward G. Ruby (Environmental Microbiology, 2010)
Summary Recent evidence has indicated that natural genetic transformation occurs in Vibrio cholerae, and that it requires both induction by chitin oligosaccharides, like chitohexaose, and expression of a putative regulatory gene designated tfoX . Using sequence and phylogenetic analyses we have found two tfoX paralogues in all sequenced genomes of the genus Vibrio . Like V. cholerae , when grown in chitohexaose, cells of V. fischeri are able to take up and incorporate exogenous DNA. Chitohexaose‐independent transformation by V. fischeri was observed when tfoX was present in multicopy. The second tfoX paralogue, designated tfoY, is also required for efficient transformation in V. fischeri , but is not functionally identical to tfoX . Natural transformation of V. fischeri facilitates rapid transfer of mutations across strains, and provides a highly useful tool for experimental genetic manipulation in this species. The presence of chitin‐induced competence in several vibrios highlights the potential for a conserved mechanism of genetic exchange across this family of environmentally important marine bacteria.

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

Predicting future threats to the long-term survival of Gila trout using a high-resolution simulation of climate change - Thomas L. Kennedy; David S. Gutzler; Ruby L. Leung (Climatic Change, 2009)

Separation of rifting and lithospheric folding signatures in the NW-Alpine foreland - O. Bourgeois; M. Ford; M. Diraison; C. Le Carlier de Veslud; M. Gerbault; R. Pik; N. Ruby; S. Bonnet (International Journal of Earth Sciences, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Discrepancies in Bacterial Recovery from Dental Unit Water Samples on R2A Medium and a Commercial Sampling Device - Richard S. Smith; Silvia A. Pineiro; Ruby Singh; Elaine Romberg; Mohamed E. Labib; Henry N. Williams (Current Microbiology, 2004)

Exposure of leopard frogs to a pesticide mixture affects life history characteristics of the lungworm Rhabdias ranae - A. D. Gendron; D. J. Marcogliese; S. Barbeau; M.-S. Christin; P. Brousseau; S. Ruby; D. Cyr; M. Fournier (Oecologia, 2003)

Sublethal Lead Affects Pituitary Function of Rainbow Trout During Exogenous Vitellogenesis - S. M. Ruby; R. Hull; P. Anderson (Archives of Environmental Contamination and Toxicology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Effects of pulse exposure to sublethal levels of hydrogen cyanide on reproduction of American flagfish - S. K. Cheng; S. M. Ruby (Archives of Environmental Contamination and Toxicology, 1981)

Hb Mobile [?2?2 73(E17)Asp ? Val]: A new variant - Rose G. Schneider; Thomas S. Hosty; Gary Tomlin; Ruby Atkins; Bernadine Brimhall; Richard T. Jones (Biochemical Genetics, 1975)